Melodi Lama dan Gelombang Baru: Studi Tentang Transisi Generasi Milenial dan Zilenial dari Radio ke Platform Musik Digital - Al Mujahid, Naqil Sayyaf; Mitra, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The rapid development of digital media platforms has transformed traditional radio listening habits, especially among Millennials and Gen Z. This shift is driven by the demand for a more personalized, accessible, and interactive experience, aligning with today’s digital lifestyle. This study applies the Diffusion of Innovations Theory and Mediatization Theory to analyze how digital platforms have reshaped music consumption. Using a qualitative phenomenological approach, data were collected through literature reviews, observations, and in-depth interviews, analyzed with the Miles, Huberman, and Saldana method. Triangulation was applied to enhance data validity. Findings indicate that accessibility, personalization, and interactive features are key factors driving the transition to digital platforms. Services like Spotify and YouTube Music offer on-demand music access with higher engagement compared to traditional radio. In conclusion, traditional radio must integrate digital technology to remain relevant. Innovations such as personalized content algorithms and social media integration can help retain audiences. Future research should explore how traditional broadcasting can evolve in the digital era.